Small furnace for the small angle X-ray scattering (SAXS) and wide angle X-ray scattering (WAXS) characterization of the high temperature carbonization of coal. Issue 4 (4th July 2021) - Wang, Yuexiang; Huang, Weifeng; Li, Zhihong; Chang, Liping; Li, Dongfeng; Chen, Rongchao; Lv, Qi; Zhao, Yixin; Lv, Baoliang
Abstract: High temperature carbonization, an important approach to cleanly and efficiently use coal, refers to a complex process in which a series of physical phenomena and chemical reactions occur when coal is heated to ≥1000 °C in anoxic conditions. A furnace was developed for the in-situ small angle X-ray scattering (SAXS) and wide angle X-ray scattering (WAXS) measurements with the scattering angle 2θ between 0° and 60° during sample heating from room temperature to 1200 °C. The usefulness of the furnace for high temperature carbonization of coal was verified at the 1W2A SAXS station at the Beijing Synchrotron Radiation Facility (BSRF).